Phage-encoded cationic antimicrobial peptide required for lysis - Holt, Ashley; Cahill, Jesse; Ramsey, Jolene; Martin, Cody; O'Leary, Chandler; Moreland, Russell; Maddox, Lori T; Galbadage, Thushara; Sharan, Riti; Sule, Preeti; Cirillo, Jeffrey D; Young, Ry (Journal of bacteriology, 2022)
Most phages of Gram-negative hosts encode spanins for disruption of the outer membrane, the last step in host lysis. However, bioinformatic analysis indicates that ∼15% of these phages lack a spanin gene, suggesting they have an alternate way of disrupting the OM. Here, we show that the T7-like coliphage phiKT causes the explosive cell lysis associated with spanin activity despite not encoding spanins. A putative lysis cassette cloned from the phiKT late gene region includes the hypothetical novel gene located between the holin and endolysin genes and supports inducible lysis in K-12. Moreover, induction of an isogenic construct lacking gene resulted in divalent cation-stabilized spherical cells rather than lysis, implicating gp in OM disruption. Additionally, gp was shown to complement the lysis defect of a spanin-null λ lysogen. Gene encodes a 56-amino acid cationic protein with predicted amphipathic helical structure and is membrane-associated after lysis. Urea and KCl washes did not release gp from the particulate, suggesting a strong hydrophobic membrane interaction. Fluorescence microscopy supports membrane localization of the gp protein prior to lysis. Gp is similar in size, charge, predicted fold, and membrane association to the human cathelicidin antimicrobial peptide LL-37. Synthesized gp behaved similar to LL-37 in standard assays mixing peptide and cells to measure bactericidal and inhibitory effects. Taken together, these results indicate that phiKT gp is a phage-encoded cationic antimicrobial peptide that disrupts bacterial outer membranes during host lysis and thus establishes a new class of phage lysis proteins, the disruptins. We provide evidence that phiKT produces an antimicrobial peptide for outer membrane disruption during lysis. This protein, designated as a disruptin, is a new paradigm for phage lysis and has no similarities to other known lysis genes. Although many mechanisms have been proposed for the function of antimicrobial peptides, there is no consensus on the molecular basis of membrane disruption. Additionally, there is no established genetic system to support such studies. Therefore, the phiKT disruptin may represent the first genetically tractable antimicrobial peptide, facilitating mechanistic analyses.